Volume 2: CFD and VIV 2014
DOI: 10.1115/omae2014-23804
|View full text |Cite
|
Sign up to set email alerts
|

A CFD Study of Focused Extreme Wave Impact on Decks of Offshore Structures

Abstract: The design of offshore structures for extreme/abnormal waves assumes that there is sufficient air gap such that waves will not hit the platform deck. Due to inaccuracies in the predictions of extreme wave crests in addition to settlement or sea-level increases, the required air gap between the crest of the extreme wave and the deck is often inadequate in existing platforms and therefore wave-in-deck loads need to be considered when assessing the integrity of such platforms. The problem of wave-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Although CNWTs are more computationally costly than their lower fidelity counterparts, CNWT experiments can deliver accurate results in high resolution, which is particularly useful for the investigation of specific flow phenomena around coastal and offshore structures. Numerous studies are reported and reviewed in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], where CNWTs are employed for the analysis of different marine engineering problems.…”
Section: Computational Fluid Dynamics-based Numerical Wave Tanksmentioning
confidence: 99%
“…Although CNWTs are more computationally costly than their lower fidelity counterparts, CNWT experiments can deliver accurate results in high resolution, which is particularly useful for the investigation of specific flow phenomena around coastal and offshore structures. Numerous studies are reported and reviewed in [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22], where CNWTs are employed for the analysis of different marine engineering problems.…”
Section: Computational Fluid Dynamics-based Numerical Wave Tanksmentioning
confidence: 99%
“…The prescribed velocities are imposed on the external part of the boundaries to represent the wavemaker and wall boundaries [16]. This can be translated to a Neumann condition in…”
Section: Potential Flow Modelmentioning
confidence: 99%
“…where U * is the boundary data which may be acquired from a wave theory [16] and n the unit normal pointing outward to the domain. Furthermore, the following dynamic and kinematic free-surface boundary conditions are imposed on Γ f PF D , [17] ∂ ∂…”
Section: Potential Flow Modelmentioning
confidence: 99%
“…By specifying complex structures such as plate breakwaters, jetties, and platforms as horizontal plates, Suchithra and Koola [20] found that the impact force generated by focused waves was larger than that of regular waves. The effect of beams under plates on wave impact was numerically addressed in another study [21]. Furthermore, the influence of structural stiffness [22], green water [23], and accompanying current [24] on freak wave action was investigated.…”
Section: Introductionmentioning
confidence: 99%